(untitled) (International Journal of Engineering and Computer Science, 2017)
In a computer architecture Cache memory have been introduced to balance performance and cost of the system. To improve the performance of a cache memory in terms of hit ratio and good response time system needs to employ efficient cache replacement policy. In this paper we proposed and implemented a novel cache replacement policy which predicts future request of a block depending upon its access pattern. Algorithm uses the concept of inter-reference recency of a block to detect access pattern and uses history of response time for efficient replacement. Result shows novel cache replacement policy has low response time and high hit ratio comparatively to other policy. Proposed policy concludes that it reduces response time and improves hit ratio.